Gauge Theory on Twisted κ-Minkowski: Old Problems and Possible Solutions - Dimitrijević, M.; Jonke, L.; Pachoł, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We review the application of twist deformation formalism and the construction of noncommutative gauge theory on κ-Minkowski space-time. We compare two different types of twists: the Abelian and the Jordanian one. In each case we provide the twisted differential calculus and consider U(1) gauge theory. Different methods of obtaining a gauge invariant action and related problems are thoroughly discussed.